Dynamics of Dissipative Solitons in a High-Repetition-Rate Normal-Dispersion Erbium-Doped Fiber Laser - Yiyang Luo; Lei Li; Luming Zhao; Qizhen Sun; Zhichao Wu; Zhilin Xu; Songnian Fu; Deming Liu (IEEE Photonics Journal, 2016)
The dynamics of dissipative solitons (DSs) are explored in a high-repetition-rate normal-dispersion erbium-doped fiber laser for the first time. Despite the high fundamental repetition rate of 129 MHz and, thus, the low pulse energy, a DS train with a dechirped pulse width of 418 fs, period doubling of single and dual DSs, and 258-MHz second-order harmonic mode locking of DSs, can be observed in the fiber laser with increasing pump power and appropriate settings. A transmitted semiconductor saturable absorber and a wavelength division multiplexer/isolator/tap hybrid module are employed to simplify the laser configuration, thus not only increasing the repetition rate but enhancing the stability and robustness of the fiber laser due to the commercial availability of all the components as well.